Communication Enhancement and Best Practices for Co-Managing Dual Care Rural Veteran Patients by VA and Non-VA Providers: A Survey Study - Shi, Jing; Peng, Yidong; Erdem, Ergin; Woodbridge, Peter; Fetrick, Ann (Journal of community health, 2014)
Many rural Veteran patients receive healthcare services from both Veterans Affairs (VA) and non-VA providers. Effective management of dual care Veteran patients to ensure the best clinical outcomes is a VA mission. The previous VA studies indicate that coordination between VA and non-VA providers has been lacking for dual care management of Veteran patients. In this study, we propose that VA proactively shares information with non-VA providers to enhance the communication process and identify the best practices to be carried out by both VA and non-VA providers for better coordination. Structured questionnaires are designed and distributed to VA and non-VA providers to obtain their evaluations on the proposed VA proactive information sharing approaches and the best practice items for dual care management. The non-VA provider respondents largely support the proposed proactive sharing items by VA, with the lowest average score being 3.96 out of a 5.0 scale on one item. In terms of the best practice items on co-managing dual care patients, three out of five items are overall rated higher than 4.0 from both sides. A pair-wise comparison between VA and non-VA perspectives further shows that the difference in average ratings of a proposed item could be significant. For such best practice items, the implementations from both sides may not be most effective.